Social Appearance Anxiety Scale: a psychometric investigation and evaluation of the influence of individual characteristics on social appearance anxiety in Brazilian adults who practice physical exercise - Donofre, Giovanna Soler [UNESP]; Campos, Juliana Alvares Duarte Bonini [UNESP]; dos Santos, Priscila Carvalho [UNESP]; Marôco, João; Campos, Lucas Arrais [UNESP]; da Silva, Wanderson Roberto [UNESP] (Frontiers, 2023)
Introduction: Evaluating signs of anxiety related to body appearance is becoming increasingly important in contemporary society and, in this sense, the Social Appearance Anxiety Scale (SAAS) seems an interesting alternative of measurement. Objectives: To evaluate the psychometric properties of the Portuguese version of the SAAS when applied to Brazilian adults who practice physical exercise and verify the influence of individual characteristics on participants’ social appearance anxiety. Methods: This was a cross-sectional study conducted online. The participants completed the SAAS and a demographic questionnaire. The psychometric properties of the SAAS one-factor model were evaluated using confirmatory factor analysis. A structural model was built for men and women to verify the influence of individual characteristics of the participants on social appearance anxiety. Results: 1,495 individuals participated in the study (70.8% women; mean age = 29.5, SD = 8.9 years). The data obtained with the SAAS presented good indicators of validity and reliability for both genders (CFI > 0.97, TLI > 0.97, SRMR = 0.04, α > 0.97, ω > 0.85). For both men and women, greater levels of social appearance anxiety were observed among younger participants, who had a higher body mass index, self-reported an eating disorder, and perceived a change in their body after the onset of the COVID-19 pandemic. For women specifically, higher income and having started physical exercise more recently were associated with greater levels of social appearance anxiety. Conclusion: The findings supported the validity and reliability of the data obtained with the SAAS and revealed that when investigating social appearance anxiety in future research and clinical protocols, specific individual characteristics should be considered.
Keywords: anxiety; physical appearance; population characteristics; structural equation modeling; validation study